TNF-α Receptor Inhibitor Alleviates Metabolic and Inflammatory Changes in a Rat Model of Ischemic Stroke - Shih-Yi Lin; Ya-Yu Wang; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Su-Lan Liao; Chun-Jung Chen (MDPI AG, 2021)
Hyperglycemia and inflammation, with their augmented interplay, are involved in cases of stroke with poor outcomes. Interrupting this vicious cycle thus has the potential to prevent stroke disease progression. Tumor necrosis factor-α (TNF-α) is an emerging molecule, which has inflammatory and metabolic roles. Studies have shown that TNF-α receptor inhibitor R-7050 possesses neuroprotective, antihyperglycemic, and anti-inflammatory effects. Using a rat model of permanent cerebral ischemia, pretreatment with R-7050 offered protection against poststroke neurological deficits, brain infarction, edema, oxidative stress, and caspase 3 activation. In the injured cortical tissues, R-7050 reversed the activation of TNF receptor-I (TNFRI), NF-κB, and interleukin-6 (IL-6), as well as the reduction of zonula occludens-1 (ZO-1). In the in vitro study on bEnd.3 endothelial cells, R-7050 reduced the decline of ZO-1 levels after TNF-α-exposure. R-7050 also reduced the metabolic alterations occurring after ischemic stroke, such as hyperglycemia and increased plasma corticosterone, free fatty acids, C reactive protein, and fibroblast growth factor-15 concentrations. In the gastrocnemius muscles of rats with stroke, R-7050 improved activated TNFRI/NF-κB, oxidative stress, and IL-6 pathways, as well as impaired insulin signaling. Overall, our findings highlight a feasible way to combat stroke disease based on an anti-TNF therapy that involves anti-inflammatory and metabolic mechanisms.